The changing work environment and the new tables of occupational diseases in Italy - Angelo SACCO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Fifteen years after the last update, the Ministry of Labor and Social Policies, in conjunction with the Ministry of Health, has released the new tables of occupational diseases in Italy with the decree of October 10, 2023. This commentary examines the modifications made, highlighting the update in knowledge related to work-related pathologies and adaptation to recent labor dynamics. It explores the attempt to simplify and make the tables more effective for use in the social insurance context and the management of occupational diseases in industry and agriculture.